CORPORATE SOCIAL RESPONSIBILITY IN INTERNATIONAL ECONOMIC LAW PERSPECTIVE - Juarsa, Nyoman Indra; Persian, Yanuarda Yudo (Faculty of Law, Universitas Brawijaya, 2015)
Multinational Corporation/MNC has a significant role to play in promoting sustainable development and alleviating global poverty. As a subject of International Economic Law, MNC has the rights to take profit from its business activities. In addition, it also has responsibility to protect sustainable environment through CSR program. This paper focuses on what more specific instrument sets CSR in international economic law, and how CSR can be implemented by the MNC. International (public) law has been providing instruments to regulate MNC activities related to CSR, those are: OECD Guidelines, ILO Declaration and UN Global Compact. However, they are only â€œsoft lawsâ€ that still require more specific instrument to be implemented. As a continuation of the general rules of public international CSR Instruments, the World Bank Group through the IFC and MIGA sets standard performances that must be met by every corporation that will get finance (IFC) or guarantee (MIGA). Standard Performances are described further in the environmental, health and safety guidelines that are essential for every company to provide protection to stakeholders related to business activities including workers, communities, and environment. As the method of evaluation and enforcement, IFC and MIGA have institution namely Compliance Advisor Ombudsman serving to receive reports from the public, investigate and provide notification to the company activities that negatively affect the society. Ultimately CSR is not only seen as philanthropy (mandatory) but also as guidelines and a code of conduct to be followed by the corporation in carrying out any business.Â Key words: mandatory norm, obligatory norm, CSR